(Bio)Propylene production processes: A critical review. Issue 4 (August 2021) - Phung, Thanh Khoa; Pham, Thong Le Minh; Vu, Khanh B.; Busca, Guido
Abstract: Production of propylene, the second-largest petrochemical after ethylene, has received considerable attention in recent years due to its wide applications and avoiding oil dependence. Many processes have been developed to produce propylene from fossil resources and renewable materials. In this review, we will introduce the current processes to produce propylene. In parallel, biopropylene production from bioethanol using a widely used material in petrochemistry, ZSM-5, has also been discussed. The physicochemical properties of ZSM-5 to be applied as an efficient catalyst for this reaction, such as the particle/crystal size, the Si/Al ratio, metal addition, and its stability, as well as reaction conditions and pathways have been discussed to suggest the potential parameters to control the bioethanol dehydration into propylene. Graphical Abstract: ga1 Highlights: Propylene production processes have been summarized. Ethanol-to-propylene (ETP) process is a promising process. ZSM-5 zeolite is a potential catalyst for the ETP process.